Epithelium-Intrinsic MicroRNAs Contribute to Mucosal Immune Homeostasis by Promoting M-Cell Maturation - Nakato, Gaku (PLoS One, 2016)
M cells in the follicle-associated epithelium (FAE) of Peyer’s patches (PPs) serve as a main portal for external antigens and function as a sentinel in mucosal immune responses. The scarcity of these cells has hampered identification of M cell-specific molecules. Recent efforts have begun to provide insight into antigen transcytosis and differentiation of M cells; however, the molecular mechanisms underlying these processes are not fully elucidated. Small non-coding RNAs including microRNA (miRNA) have been reported to regulate gene expression and control various biological processes such as cellular differentiation and function. To evaluate the expression of miRNAs in FAE, including M cells, we previously performed microarray analysis comparing intestinal villous epithelium (VE) and PP FAE. Here we confirmed FAE specific miRNA expression levels by quantitative PCR. To gain insight into miRNA function, we generated mice with intestinal epithelial cell-specific deletion of Dicer1 (Dicer(ΔIEC)) and analyzed intestinal phenotypes, including M-cell differentiation, morphology and function. Dicer(ΔIEC) mice had a marked decrease in M cells compared to control floxed Dicer mice, suggesting an essential role of miRNAs in maturation of these cells. Furthermore, transmission electron microscopic analysis revealed that depletion of miRNA caused the loss of endosomal structures in M cells. In addition, antigen uptake by M cells was impaired in Dicer(ΔIEC) mice. These results suggest that miRNAs play a significant role in M cell differentiation and help secure mucosal immune homeostasis.